Effect of spraying with normal and Nano NPK fertilizers and their in-terference in growth indicators of strawberry seedlings Fragaria ana-nassa Duch. Ruby gem cultivar - Abdullah, Kadum; Amran, Hisham Aziz; Kadhim, Zaid Khaleel; Lateef, Sabreen Mohammed (Journal of Kerbala for Agricultural Sciences, 2021)
This field study was carried out in the plastic canopy of the Dept. of Horticulture and Landscape, College of Agriculture / University of Kerbala on 2019 (during spring season). The design of the experiment was a Randomized Complete Block Design (RCBD) with three replications. The experiment included nine treatments resulting from the combinations among three concentrations of the regular NPK fertilizer (0, 3, and 6) g. l-1 with NPK nano-fertilizer (0, 1.5, and 3) g. l-1 in order to investigate the impact of foliar addition with these single and combined treatments on strawberry plants cultivar Ruby gem. The results showed that the spraying of the NPK nano fertilizer in combination with the regular fertilizer NPK (at different combinations) had a significant effect on the leaf area and the content of leaves from chlorophyll (985 cm2, 44.27 SPAD) respectively, which was reflected on the fruit yield and quality represented by the size, length, diameter and weight of the fruit (17.67 cm3, 37.87 mm, 32.92 mm, 15.13g) respectively in addition to the content of the fruits of total soluble solids and lycopene pigment (17.00%, 0.1890 mg/100 ml) respectively. It could be concluded that it is possible to rely on the use of modern nano-fertilizer technology combined with normal fertilizer in low quantities of recommendations to reach the optimal production of various agricultural crops and reduce the environmental impact by severe usage of the fertilizer’s recommendations.